Dynamic Behavior of a Stochastic Amensalism Population Model - AI Xiao-hui; DENG Wen-bo; LI Peng-zhe (Journal of Harbin University of Science and Technology, 2022)
Aiming at the problem of biased symbiosis dynamics affected by environmental factors, according to the theory of stochastic differential equation, the stochastic biased symbiosis dynamics model is established by introducing white noise, and the dynamic behavior of the stochastic biased symbiosis population model is studied. Firstly, the existence of global positive solution of the stochastic partial hazard symbiosis dynamics model is proved. Secondly, the stochastic ultimate boundedness of the solution of the stochastic partial hazard symbiosis dynamics model is proved by using the Ito^ formula and Chebyshev inequality. Thirdly, the asymptotic properties of the moment of the solution of the stochastic partial hazard symbiosis dynamics model are analyzed. Finally, the theoretical results are verified by numerical simulation.